Strategies and development of quality assurance and control in the ELSA-Brasil - Schmidt, Maria Ines; Griep, Rosane Harter; Passos, Valeria Maria; Luft, Vivian Cristine; Goulart, Alessandra Carvalho; Menezes, Greice Maria de Souza; Molina, Maria del Carmen Bisi; Vigo, Alvaro; Nunes, Maria Angelica (Revista de Saúde Pública, 2013)
The ELSA-Brasil (Estudo Longitudinal de Saúde do Adulto - Brazilian Longitudinal Study for Adult Health) is a cohort study composed of 15,105 adults followed up in order to assess the development of chronic diseases, especially diabetes and cardiovascular disease. Its size, multicenter nature and the diversity of measurements required effective and efficient mechanisms of quality assurance and control. The main quality assurance activities (those developed before data collection) were: careful selection of research instruments, centralized training and certification, pretesting and pilot studies, and preparation of operation manuals for the procedures. Quality control activities (developed during data collection and processing) were performed more intensively at the beginning, when routines had not been established yet. The main quality control activities were: periodic observation of technicians, test-retest studies, data monitoring, network of supervisors, and cross visits. Data that estimate the reliability of the obtained information attest that the quality goals have been achieved.